10Be Exposure Ages Obtained From Quaternary Glacial Landforms on the Tibetan Plateau and in the Surrounding Area. (27th April 2018) - ZHANG, Mengyuan; MEI, Jing; ZHANG, Zhigang; WANG, Jian; XU, Xiaobin
Abstract : Abstract: In situ terrestrial cosmogenic nuclide (TCN) exposure dating using 10 Be is one of the most successful techniques used to determine the ages of Quaternary deposits and yields data that enable the reconstruction of the Quaternary glacial history of the Tibetan Plateau and the surrounding mountain ranges. Statistical analysis of TCN 10 Be exposure ages, helps to reconstruct the history of glacial fluctuations and past climate changes on the Tibetan Plateau, differences in the timing of glacier advances among different regions. However, different versions of the Cosmic‐Ray‐prOduced NUclide Systematics on Earth (CRONUS‐Earth) online calculator, which calculates and corrects the TCN ages of Quaternary glacial landforms, yield different results. For convenience in establishing contrasts among regions, in this paper, we recalculate 1848 10 Be exposure ages from the Tibetan Plateau that were published from 1999 to 2017 using version 2.3 of the CRONUS‐Earth calculator. We also compare the results obtained for 1594 10 Be exposure ages using different versions (2.2, 2.3 and 3.0) of the CRONUS‐Earth calculator. The results are as follows. (1) Approximately 97% of the exposure ages are less than 200 ka. A probability density curve of the exposure ages suggests that greater numbers of oscillations emerge during the Holocene, and the peaks correspond to the Little Ice Age, the 8.2 ka and 9.3 ka cold events; the main peak covers the period between 12 and 18 ka. (2) In most areas, the newer versions of the calculator produce older 10 Be exposure ages. When different versions of the CRONUS‐Earth calculator are used, approximately 29% of the 10 Be exposure ages display maximum differences greater than 10 ka, and the maximum age difference for a single sample is 181.1 ka.